Dyke/Girl: Language and Identities in a Lesbian Group - Jones, L. author. aut Link
VIII, 195 p.
Keywords: This book explores the construction of identities within a lesbian group, outlining interactive tactics used in the production of mutually-negotiated norms of authenticity. Using ethnography and discourse analysis, a range of group-specific personae are revealed to be continually reworked and reproduced within the women's interaction.